Push Notifications Studies in the Last Decade : A Bibliometric Analysis - Nurwidi Bagus Amiryunanto; Mery Citra Sondari (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study aims to provide a comprehensive overview of the development of research on push notifications over the past decade through a bibliometric approach. Push notifications have become a crucial feature across various digital platforms, including mobile applications, e-commerce systems, educational tools, and social communication services. However, systematic reviews that explore research trends, dominant thematic areas, and key contributing authors and institutions remain limited. Utilizing the Scopus database, this study collected and analyzed 250 scholarly publications published between 2013 and 2023. The bibliometric techniques applied include publication productivity analysis, co-authorship and co-citation mapping, as well as keyword co-occurrence analysis to identify popular topics and their evolution over time. The findings reveal a significant rise in publication volume beginning in 2017, coinciding with the rapid development of mobile technologies and machine learning applications. The most frequently discussed themes include message personalization, user engagement, data privacy, and notification-based recommendation systems. Countries such as the United States, China, and India emerged as dominant contributors in terms of publication output and research collaborations. This bibliometric analysis offers valuable insights for researchers, app developers, and policymakers interested in understanding the direction of push notification research and its practical implementations. The results also serve as a foundation for future studies in the fields of human-computer interaction, user experience design, and data-driven technologies. Additionally, this study identifies gaps in the current literature, such as ethical concerns and long-term user behavioral impacts, which warrant deeper investigation. Future research may benefit from interdisciplinary approaches combining technology, psychology, and communication studies.